2019
DOI: 10.1071/rd19103
|View full text |Cite
|
Sign up to set email alerts
|

Shift from slow- to fast-twitch muscle fibres in skeletal muscle of newborn heterozygous and homozygous myostatin-knockout piglets

Abstract: Myostatin (MSTN) is a member of the transforming growth factor-β superfamily that negatively regulates skeletal muscle development. A lack of MSTN induces muscle hypertrophy and increases formation of fast-twitch (Type II) muscle fibres. This study investigated muscle development in newborn heterozygous (MSTN+/−) and homozygous (MSTN−/−) MSTN-knockout piglets. Detailed morphological and gene and protein expression analyses were performed of the biceps femoris, semitendinosus and diaphragm of MSTN+/−, MSTN−/− a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…Combined with previous study, the transformation of muscle fiber type may be related to the downregulation of MSTN expression. Different from the results of this experiment, Xuan et al's (2019) study found that when MSTN was knocked out, the proportion of Type II and Type I muscle fibers of piglets increased and decreased respectively. But at the same time, the authors also indicate that the change of muscle fiber type is regulated by a variety of specific genes, among which MRFs and MEF2 occupy the core position in the regulation of muscle fiber.…”
Section: Discussioncontrasting
confidence: 83%
“…Combined with previous study, the transformation of muscle fiber type may be related to the downregulation of MSTN expression. Different from the results of this experiment, Xuan et al's (2019) study found that when MSTN was knocked out, the proportion of Type II and Type I muscle fibers of piglets increased and decreased respectively. But at the same time, the authors also indicate that the change of muscle fiber type is regulated by a variety of specific genes, among which MRFs and MEF2 occupy the core position in the regulation of muscle fiber.…”
Section: Discussioncontrasting
confidence: 83%
“…Protein PGC-1α stimulates not only mitochondria biogenesis and more efficient fatty acid oxidation but also irisin mRNA expression [35]. Particularly important is that myostatin promotes the remodeling of muscle tissue to increase the expression of the slow myosin heavy-chain isoform and inhibits the formation of the fast chain isoform (type II, anaerobic) [77,78]. In this context, the increase in plasma myostatin in response to exercise in horses could have a negative impact on the increase in the fast myosin heavy chain isoform, thereby protecting the organism against the overproduction of lactic acid.…”
Section: Discussionmentioning
confidence: 99%
“…One of these MSTN -edited models, its progeny, or its crosses were further investigated . These include investigations on fiber-type distribution and expression of myosin heavy chain isoforms; shift from slow- to fast-twitch muscle fibers in skeletal muscle; internal organ size; semen quality and fertilization ability; reproductive trait characterization in MSTN -edited crosses; collagen-related pathological features (umbilical hernia and tippy toe standing); regulation of body fat deposition; fibrinogen levels and fibrin clot structure; esophageal striated muscle development and regulation of muscle fiber types; extraocular muscles; cardiac extracellular matrix; growth of smooth muscle in uterine horns of MSTN mutant gilts; smooth muscle content in corpus cavernosum of MSTN mutant boars; erythrocyte osmotic fragility, hematological parameters, and fatty acid composition of serum and erythrocyte membranes; miR-455-3p regulation of myoblast differentiation; composition and alteration of gut microbiota; analysis of meat and fatty acids characteristics; and development of a restriction enzyme-mediated PCR-RFLP assay for genotyping MSTN mutant pigs …”
Section: Targeting the Mstn Gene In Pigsmentioning
confidence: 99%